Sustainability-focused rural tourism development in Western Serbia - Vesić Marina; Savić Marijana; Pavlović Sanja; Bolović Jelena (Glasnik Srpskog Geografskog Društva, 2022)
Rural tourism is seen as one of the aspects of sustainable economic growth and socio-cultural development of rural Serbia. During the Covid-19 pandemic, international tourist traffic declined, and tourism and hospitality as service activities suffered serious economic consequences. The aim of this paper is to examine the impact of pandemics on rural areas of Western Serbia, bearing in mind that the natural environment and rural areas have gained in importance as safer to live in. The research was conducted through an electronic questionnaire, by surveying the providers of catering services in this part of Serbia. The obtained results indicate a decline in the number of tourists (domestic and foreign) during the pandemic, but mostly positive attitudes of service providers regarding the prospects and sustainability of their business in the coming period. The data obtained in this research can be useful to local governments and tourism representatives in finding the best solutions to provide support to the bearers of the tourist offer of rural areas.